Access to justice and citizenship in old age. Contributions and reflections from a university project in Santa Fe, Argentina - Marzioni, Sofía Clarisa (2025)
Based on the experience of the Project “Older People: Rights and policies for a good aging” of the Faculty of Legal and Social Sciences (National University of the Litoral in Santa Fe, Argentina), the work addresses the state of the situation regarding access to justice for older people. Likewise, it presents legislative initiatives designed to guarantee speed in judicial processes and train public officials. It highlights the need for different institutions and social groups - including the public University - to join forces to overcome the structural problems that hinder the exercise of the rights of older people.